2017
DOI: 10.1016/j.ijrobp.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of a Phase 1 Dose-Escalation Trial for Early-Stage Breast Cancer Using 5-Fraction Stereotactic Body Radiation Therapy for Partial-Breast Irradiation

Abstract: Dose was escalated to the target dose of 40 Gy in 5 fractions, with the occurrence of only 1 dose-limiting toxicity. Patients felt cosmetic results improved within the first year after surgery and stereotactic body radiation therapy. Our results show minimal toxicity with excellent cosmesis; however, further follow-up is warranted in future studies. This study is the first to show the safety, tolerability, feasibility, and cosmesis results of a 5-fraction dose-escalated S-PBI treatment for early-stage breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 37 publications
2
65
0
Order By: Relevance
“…Dose constraints used in this report ( Table 2 ) were based on TG 101 and the recently reported phase 1 dose escalation trial for early stage breast cancer using 5-fraction (maximum dose of 40 Gy) stereotactic body radiation therapy for partial-breast radiation. 14 , 17 This phase 1 dose escalation trial reported excellent clinical outcomes, minimal toxicity, and good cosmesis using these OAR dose constraints. 14 An additional chest wall dose constraint was applied on the basis of Memorial Sloan Kettering data evaluating the risk of chest wall toxicity in patients treated with 5-fraction stereotactic body radiation therapy for early stage non-small cell lung cancer.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…Dose constraints used in this report ( Table 2 ) were based on TG 101 and the recently reported phase 1 dose escalation trial for early stage breast cancer using 5-fraction (maximum dose of 40 Gy) stereotactic body radiation therapy for partial-breast radiation. 14 , 17 This phase 1 dose escalation trial reported excellent clinical outcomes, minimal toxicity, and good cosmesis using these OAR dose constraints. 14 An additional chest wall dose constraint was applied on the basis of Memorial Sloan Kettering data evaluating the risk of chest wall toxicity in patients treated with 5-fraction stereotactic body radiation therapy for early stage non-small cell lung cancer.…”
Section: Methodsmentioning
confidence: 91%
“… 14 , 17 This phase 1 dose escalation trial reported excellent clinical outcomes, minimal toxicity, and good cosmesis using these OAR dose constraints. 14 An additional chest wall dose constraint was applied on the basis of Memorial Sloan Kettering data evaluating the risk of chest wall toxicity in patients treated with 5-fraction stereotactic body radiation therapy for early stage non-small cell lung cancer. 18 …”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, this is the first study summarizing the practice and technological considerations of GYN SABR among experts that practice and have published on this technique [8,[10][11][12][13][14][15][16][17][18][19][20][21]. It is not intended to serve as a consensus guideline.…”
Section: Discussionmentioning
confidence: 99%